Messung der gefühlten Inflation in Deutschland - Johannes Treu; Johannes Hartwig (IU Internationale Hochschule, 2022)
– This paper shows that there is a very large difference between the official measured inflation rate with its basket of 650 types of goods and perceived inflation in Germany. While the inflation rate in Germany was 10.0% in September 2022 and 10.4% in October, a nationwide survey revealed that respondents perceived inflation to be 34.15%. At the same time, the paper provides an explanatory approach to explain the perceived inflation using a regression model. It becomes clear that all independent variables are highly significant and provide an explanatory contribution. It also shows that higher inflation concerns lead to a higher estimate of perceived inflation.
Keywords: E3; E31; 330; Inflation; Gefühlte Inflation; Inflationserwartungen; Inflationsmessung